Employee Performance at the Semarang District Social Service and Education Level - Puspita Puji Rahayu (Jurnal Visi Manajemen, 2020)
Global environmental changes have increased the complexity and disarray of the competitive environment, resulting in severe competition and placing pressure on each player to hone their creative business skills. At this point, the company realized that using its human resources would be its last remaining option for resolving the problem. In other words, enhancing organizational performance motivates staff to produce top-notch work. As a result, from the beginning of the job relationship until it is over, efforts must be made effectively. Discipline may motivate workers to carry out any duty successfully. Therefore, you must try to become an expert in the discipline. This study set out to determine how much the employees' level of education and work ethic influenced their performance at the Semarang District Social Service. The data used in this inquiry were based on the survey's fundamental information. The sample for the study consisted of every employee of Semarang District Social Service.